Gordana Blagojević, Η μουσική μεταρρύθμιση του 1814: μια εμπειρική-αφηγηματολογική προσέγγιση [The musical reform of 1814: an empirical-narratological approach] - Plemmenos, John (Гласник Етнографског института САНУ; Издање 68 Број 3 (2020): Ислам, појединац и делатне заједнице у Србији: актери промена, сукоба и сарадње, 2021)
Gordana Blagojević, Η μουσική μεταρρύθμιση του 1814: μια εμπειρική-αφηγηματολογική προσέγγιση [The musical reform of 1814: an empirical-narratological approach] Τμήμα Μουσικών Σπουδών της Φιλοσοφικής Σχολής του Εθνικού και Καποδιστριακού Πανεπιστημίου Αθηνών, «Εργαστήριο Βυζαντινής Μουσικολογίας», Αθήνα 2019 [Department of Music Studies of the Faculty of Philosophy of the National and Kapodistrian University of Athens, “Laboratory of Byzantine Musicology”, Athens 2019]. ISBN 978-618-83987-1-9 It is admittedly not an easy task for someone to evaluate properly and convincingly the work of an eminent colleague who is also well- and long-known to him. The reviewer may then be misguided (un- or subconsciously) by his feelings or sentiments, and so miss his target: an unbiased and well-balanced judgement. What is more, Gordana Blagojević, author of the work under review, has long been a spottable and distinguishable figure in the Greek academia and the reading public through her numerous participations in conferences organised in Greece and her equally innumerable admittances in Greek libraries and research centres. Yet, I will try, as the legendary Ulysses did, to shut my ears before the melodious sirens of intimacy and collegiality. But, I am afraid I will not be able, despite Roland Barthes’ insisting calls, to “kill” the author1 in order to study unbiased her work per se: an impossible task!